Modern organic synthesis : - Zweifel, George S. (W.H. Freeman, 2007)
Written for the organic synthesis portion of the advanced organic chemistry course (taken by seniors and graduate students), Zweifel and Nantz's concise new text covers the essentials with exceptional coherence and clarity without bogging students down with too much unnecessary material.